Implementasi Manajemen Berbasis Madrasah dalam Meningkatkan Outpu/Lulusan Siswa di MA Mathlaul Anwar Kepuh Serang - Mohammad Farkhan (MANAZHIM, 2021)
This study was conducted to determine how the implementation of madrasa-based management and the results of this implementation in increasing the output/graduates of students at MA Mathlaul Anwar Kepuh Serang Banten. This research is a type of descriptive qualitative research. Data were collected by means of interviews, field observations, and documentation. Data analysis was carried out by reducing data from interviews, then presenting data and finally drawing conclusions as a form of answers to the background of the research problem. The implementation of madrasa-based management at MA Mathlaul Anwar Kepuh Serang Banten includes, curriculum management, student management, management of educators and education, management of facilities and infrastructure, financial management, and management of relations with the community running well from planning to evaluation. The implementation of madrasa-based management in increasing student output/graduates at MA Mathlaul Anwar Kepuh is generally carried out well, as evidenced by the presence of several students who can continue their education at public and private universities. There are even some students who can continue their studies with the tahfidz scholarship program abroad. Being able to improve students' non-academic achievements can be seen from the increasing achievements achieved by MA Mathlaul Anwar Kepuh even though they have not been able to improve academic achievement at MA Mathlaul Anwar seen from the lack of increase in UN scores from the previous year.